THE DEVELOPMENT OF COOPERATIVE LEARNING MODELS OF THINK PAIR SHARE TYPE IN THE MAHARAH KITABAH OF STUDENTS IN VII CLASS SMPU BP AMANATUL UMMAH MOJOKERTO - Saebatul Hamdi N. M; Muhammad Afthon Ulin Nuha (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
Think Pair Share is one a type of cooperative learning model designed to influence the pattern of student interactions in learning. The kind that used of this research is Research and Development (R n D), using ADDIE model. For the stages of development are : 1) Analyze Stage, 2) Design Stage, 3) Development Stage, 4) Evaluation Stage. The results show that (1) research development produce a learning implementation plan ( RPP ) cooperative learning model think pair share type to increase maharah kitabah or writing skills students of VII class SMPU BP Amanatul Ummah Mojokerto. 2) the result of this reserach and development of learning implementation plan (RPP) meets the criteria is valid, be using formulation likert scalen P=F/N × 100. The resluts of the first validator is 61% and the second validator is 71 %. Therefore, this learning implementation plan (RPP) cooperative learning models think pair share type to increase maharah kitabah or writing skills students of VII class is feasible and be used.